2004
DOI: 10.1021/ma035668n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of an A/B/C Triblock Copolymer for Battery Materials Applications

Abstract: An A/B/C triblock copolymer has been synthesized having potential applications as a self-contained nanoscale battery. A new organometallic compound was synthesized which serves as the anode. The polyelectrolyte block of the copolymer is an unsaturated polyether. The last block acts as the template to form metal oxide clusters and functions as the cathode. The triblock copolymer was synthesized by ring-opening metathesis polymerization using Grubbs's catalyst. GPC and NMR were used to monitor the polymerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…The thermodynamic self-assembly of a poly(ethylene oxide)-based block copolymer can also provide a template for incorporation of gold salts or nanotubes to create a self-organizing, nanocomposite electrode [97]. Bullock and Kofinas have used ionically conducting block copolymers as templates for the synthesis of lithium manganese oxide nanoparticles such that a self-assembled film functions as both a polyelectrolyte and as a composite anode in a lithium battery system [98,99].…”
Section: Ordering Of Functional Block Copolymersmentioning
confidence: 99%
“…The thermodynamic self-assembly of a poly(ethylene oxide)-based block copolymer can also provide a template for incorporation of gold salts or nanotubes to create a self-organizing, nanocomposite electrode [97]. Bullock and Kofinas have used ionically conducting block copolymers as templates for the synthesis of lithium manganese oxide nanoparticles such that a self-assembled film functions as both a polyelectrolyte and as a composite anode in a lithium battery system [98,99].…”
Section: Ordering Of Functional Block Copolymersmentioning
confidence: 99%
“…Catalyst 2 was used as the initiator producing a polymer with an PDI of 2. [33] Initiator 7 and initiator 8 have already been tested for their potential in block copolymer synthesis. Both initiators, as already outlined, provide complete initiation and an outstanding functional-group tolerance and are particularly suited for block copolymer synthesis, as evidenced by a combined matrix-assisted laser desorption/ionisation mass spectroscopic, gel permeation chromatographic, and NMR spectroscopic studies of an ABC triblock cooligomer prepared by 7 (Table 5: entry 1).…”
Section: Realising Different Polymer Architecturesmentioning
confidence: 99%
“…The glycomonomer depicted in Scheme 7 was polymerised under emulsion conditions in a dichloroethane Scheme 5. Block copolymers described in reference [32] (left; P indicates the same polymer chains as the one shown) and reference [33] (right). water mixture in the presence of dodecyltrimethylammonium bromide as the detergent.…”
Section: Realising Different Polymer Architecturesmentioning
confidence: 99%
“…Kofinas et al reported on synthesis, characterization and applications of poly(NBECOOH)-based amphiphilic block copolymers. [25][26][27] As living polymerization chemists' point of view, however, the diagnostic proof for the absence of chain transfer and termination has not been clearly provided so far. So, it intrigued us to study systematically on living ROMP of NBETMS to achieve hydrophilic poly (NBECOOH) with controlled molecular weight and narrow molecular weight distribution.…”
Section: Mnmentioning
confidence: 99%